Infrared Aerial Photograph Application for Prediction of Runoff Coefficient at Wuryantoro Catchment, Wonogiri - Santoso, Sugiharto Budi (Forum Geografi, 2002)
This research was carried out in Wuryantoro Watershed, Wonogiri. The goal of this study is to examine the remote sensing technology capability to obtain the physical characteristics data of watershed in the prediction of runoff coefficient using cook method. The physical characteristics is topography (relief), landcover, water storage, and infiltration. The physical characteristis is interpreted on infrared aerial photography on scale 1 : 10.000 based on element of interpretation i.e. tone, texture, size, shape, pattern, site, and association. The result of the prediction is tested by comparing them with the data of field measurement result. The accuraccy of the result of aerial photo interpretation of physical characteristics of watershed can be obtained as follows 1) the accuracy of the interpretation of landuse 88,5%; 2) the accuracy of slope interpretation 87.67%. The accuracy of prediction of the runoff coeficient 86.9%.